Development of a microecologic product from Lactobacillus rhamnosus based on silica. (11th July 2022) - Wu, Wanqin; Liu, Guanwen; Li, Huixin; Yang, Rongrong; Ai, Chongyang; Pang, Bing; Jiang, Chunmei; Shi, Junling
Abstract: Background: Probiotics are primarily made into microecologic products for use in the food and feed industries. The freeze‐drying technique is widely used in their preparation to maintain their high level of bioactivity. This causes high costs in terms of the energy and time needed. In this study, we developed a method to produce a highly active microecologic product from Lactobacillus rhamnosus using heating and silica. Results: A microecologic product was made successfully from L. rhamnosus using the whole bacterial culture broth, without waste, and using food‐grade silica (4.5 mL g −1 ) to absorb water before drying at 37 °C for 8 h. The activity of L. rhamnosus cells was increased significantly by adding water extracts of green tea to the culture medium. The viable amount of L. rhamnosus in the obtained microecologic product was 9.80 × 10 10  cfu g −1 with a survival rate of 224.67% in simulated gastric juice for 3 h and 68.2% in simulated intestinal juice for 3 h. The microecologic product treated an intestinal infection by multi‐drug‐resistant Staphylococcus aureus in mice very efficiently. Conclusion: The study developed an economic, eco‐friendly, and efficient method for preparing highly active microecologic agents using heating and without waste. © 2022 Society of Chemical Industry.